Evolución de la Capilla Real de Palacio en la segunda mitad del siglo XVIII - Saavedra Zapater, Juan Carlos (Cuadernos de Historia Moderna, 2003)
The objective of present work is to study the situation of the Royal Chapelle during last 50 years of XVIIIth century, in which is remarkable, on one hand, the reform conducted by marquis of Ensenada, included in the general reform of Royal Houses, and, on the other hand, the constitution of Royal Chapell as a parish by papal bull of Bebedicto XIV in 1753. Theese two facts will represent the referents in the evolution of this institution during that period.